Change in technology-enabled omnichannel customer experiences in-store. (March 2022) - Alexander, Bethan; Kent, Anthony
Abstract: This paper explores changes in technology-enabled omnichannel customer experiences in stores over a five-year period (2014–2019). It contributes to the omnichannel-experience-management literature through customer technology-enabled touchpoints within fashion retail. Adopting an exploratory qualitative approach, primary data were obtained using semi-structured interviews with millennial consumers. The findings demonstrate the growing importance of implementing and integrating in-store technologies to improve customer experience. From these, two models are developed: "technology-induced customer experience in-store"; and "technology-enabled customer shopping journey in-store".